Klaudiusz Elian o nazwach młodych zwierząt („De natura animalium” VII 47) - Kaczyńska, Elwira (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
In his work entitled On the Characteristics of Animals (VII 47), Claudius Aelianus discusses numerous Ancient Greek names of wild animals, especially their young. He registers as many as 18 different appellatives referring to young animals as well as ten poetic or dialectal terms for mature ones. The aim of the present study is to analyze the Ancient Greek words denoting young animals quoted by the Roman writer from the viewpoint of etymology and word-formation.